Limits of the Supervisory Jurisdiction of the Office of Financial Supervision on Administrative Contracts in the Kurdistan Region - Iraq: An analytical study - Fares, Ruqya Othman; Zangna , Esmael Najmadin (The Scientific Journal of Cihan University– Sulaimaniya, 2022)
The provisions of control, in its various forms, on the work of state institutions is regarded as a basic pillar for protecting the principle of legality and the rule of law, and financial control, which is represented in a set of procedures aimed at evaluating the work of the state through monitoring the implementation of government plans and programs, this has great importance in preventing or limiting the occurrence of Financial violations. The entity assigned with the financial control process pursues the financial violations of these institutions by ascertaining and checking the disbursement of funds from the state’s general budget, as well as controlling the state’s actions (The Administration) which is of a financial nature by looking at records and accounting revenues. The Office of Financial Supervision is one of the most important financial control institutions in the Kurdistan Region - Iraq, as its laws stipulate that the Bureau enjoys the jurisdiction of financial control over the financial and administrative actions of the region’s institutions, and among those actions are administrative contracts. The contracting administration shall abide by the laws and instructions and embody in its contractual work the principle of legality to ensure the proper application of the law and the protection of public and private funds of the state. The aim of writing this research is to clarify the limits of that control in the various stages of concluding and implementing the administrative contract, and to clarify the role of the Bureau in any of those stages. And this is in the context of a tight research plan until the research reaches its conclusion represented by the most prominent conclusions and research outcomes, as well as the proposals and recommendations put forward in it, and that is in order to fill the shortcomings and defects, and, further to develop this type of oversight by maximizing the role of the Board of Financial Audit in the provisions of its control over the contractual administrative operations and that is before and after implementation.